Optimizing the IoT and big data embedded smart supply chains for sustainable performance - Pratap S.; Jauhar S.K.; Gunasekaran A.; Kamble S.S. (My University, 2025)
A sustainable and robust supply chain is becoming increasingly important to meet customers’ never-ending needs. Numerous supply chain challenges such as forecasting issues, maintaining traditional inventories, distribution delays, delayed digital transformation, counterfeit consumer goods, excessive carbon gas emissions, and hazardous waste have necessitated improvements in supply chain management. These difficulties can only be addressed by modernizing the embedded technology of the supply chain. According to current assessments, organizations should prioritize sustainable development and use innovations such as the “Internet of Things (IoT) and big data” to create smart and resilient supply chains for sustainable performance and Industry 4.0. Industry 4.0, ushers in a sustainable and digital supply chain revolution through the application of cutting-edge technologies. The 19 papers in this special issue aim to contribute to the development of research topics on optimizing the IoT and big data-embedded smart supply chains for sustainable performance. Three major macro-topics arose: (i) Implication of IoT in Supply Chain, (ii) impact of big data in the supply chain, and (iii) Use of Blockchain in Supply Chain Analysis. Novel evidence-based frameworks and approaches have been proposed, as well as some real-life situations, in the articles featured in this special issue collection, supporting meaningful developments in the twin subject of IoT and Big data-embedded smart supply chains for sustainable performance. Nonetheless, an examination of the papers in the special issue reveals interesting research prospects required to analyze and explore this developing topic in terms of its various features. More evidence and application-based research are required to better understand the dynamics of Smart Supply Chains for Sustainable Performance ecosystems and Industrial Symbiosis networks. Finally, specialized IoT and Big data are being developed. Embedded solutions based on intelligent architectures and data-driven techniques can help firms embrace Smart Supply Chains for Sustainable Performance not only within their own walls, but also in the supply chain and societal dimensions. © 2023